(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Modern methods in teaching foreign languages have revolutionized the way individuals learn and master a new language. These methods have replaced traditional approaches and have proven to be more effective and engaging for learners. In this article, explained the importance of modern methods in teaching foreign languages and discuss their impact on language acquisition